The Effect of Digitizing Library Services and Facilities on User Satisfaction - Amad Mutawali; Sakti Alamsyah; Unin Nibi Saputra (International Journal of Economics (IJEC), 2023)
Digitization of library services and facilities is a factor that can increase user satisfaction. The purpose of this study is to determine the effect of digitization of library services and facilities on user satisfaction. This research data is from users at the Regional Library of Cianjur Regency with a population of 1,000. The sampling technique in this study used a sample size web.raosoft.com with an error rate of 5% so that a sample of 287 respondents was obtained. Disseminating questionnaires is a method of data collection. This study used multiple linear regression analysis as its analysis method. The results showed that the digitalization of library services and facilities had a positive effect on user satisfaction, and the effect was 38.8% while 61.2% was influenced by other variables. The variable that has a dominant influence is library facilities, with an influence of 16%. The contribution of this study is to expand marketing management literature related to the digitization of library services and facilities in the context of organizations.